Pengelolaan Gangguan Mobilitas Fisik Dengan Range Of Motion Pasif Kombinasi Mirror Therapy Pada Stroke Iskemik di Rs. Soerojo Magelang: Management of Physical Mobility Impairment Using Passive Range of Motion Combined with Mirror Therapy in Ischemic Stroke Patients at Soerojo Hospital, Magelang - Muhanifah, Lutfi Muhanifah; Susilo, Tri Susilo (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Ischemic stroke is one of the leading causes of physical disability in Indonesia, with a prevalence that continues to increase annually. Impaired physical mobility due to stroke results in decreased movement ability, primarily caused by muscle weakness and body imbalance. Although various interventions have been applied in nursing practice, there is still a research gap regarding the effectiveness of combining passive Range of Motion (ROM) exercises and mirror therapy in improving the physical mobility of ischemic stroke patients. This study aims to evaluate the effectiveness of managing physical mobility impairment through a combination of passive ROM and mirror therapy in ischemic stroke patients. This study employed a case study design with a nursing care approach. The subject was a patient diagnosed with ischemic stroke undergoing treatment at Prof. Dr. Soerojo Hospital, Magelang. Data were collected in June 2025 using nursing assessment forms, muscle strength observations, and documentation of interventions and evaluations. The intervention was carried out over three days using a structured application of passive ROM and mirror therapy. Data were analyzed descriptively by comparing the patient's muscle strength before and after the intervention. This study obtained ethical approval from the educational institution and hospital. The results showed that the patient experienced an improvement in left extremity muscle strength from scale 0 (no muscle contraction) to scale 1 (visible muscle contraction without movement), indicating enhanced mobility function. This finding was supported by the nursing evaluation table, which showed improved movement ability during the three-day intervention. Compared to previous studies, these findings are consistent with the known effectiveness of mirror therapy in stimulating neuroplasticity, while passive ROM helps maintain joint flexibility and muscle tone. However, challenges such as patient fatigue and limited implementation time posed obstacles to therapy continuity. This study concludes that the combination of passive ROM and mirror therapy is effective in addressing physical mobility impairments in ischemic stroke patients and can serve as an alternative intervention in rehabilitative nursing practice, especially in stroke care units. Nevertheless, further research with larger sample sizes and longer intervention periods is needed to generalize these findings.